2019
DOI: 10.3389/fpsyg.2019.02486
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the Acceptability and Felicity of English Negative Dependencies: Where Negative Concord and Negative Polarity (Do Not) Overlap

Abstract: Negative Concord (NC) constructions such as the news anchor didn’t warn nobody about the floods (meaning “the news anchor warned nobody”), in which two syntactic negations contribute a single semantic one, are stigmatized in English, while their Negative Polarity Item (NPI) variants, such as the news anchor didn’t warn anybody about the floods, are prescriptively correct. Because acceptability is often equated with grammaticality, this pattern has led linguists to treat NC as ungrammatical in “Standard” or sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 59 publications
(98 reference statements)
3
18
0
Order By: Relevance
“…The three nonce verbs were "jeck", 6 More specifically, Standard English speakers have been shown to accept both NC and DN readings in their language, as a function of the syntactic, pragmatic and intonational properties of the relevant sentence. For example, adult English speakers are more likely to accept NC interpretations for sentences where the negative marker scopes above the negative indefinite (e.g., 'John didn't call nobody') than for sentences where the negative indefinite has wide scope (e.g., 'Nobody didn't call') (Blanchette 2019). 7 All experimental hypotheses, predictions, and analyses, were preregistered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three nonce verbs were "jeck", 6 More specifically, Standard English speakers have been shown to accept both NC and DN readings in their language, as a function of the syntactic, pragmatic and intonational properties of the relevant sentence. For example, adult English speakers are more likely to accept NC interpretations for sentences where the negative marker scopes above the negative indefinite (e.g., 'John didn't call nobody') than for sentences where the negative indefinite has wide scope (e.g., 'Nobody didn't call') (Blanchette 2019). 7 All experimental hypotheses, predictions, and analyses, were preregistered.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent experimental results suggest that speakers of Standard English can consistently generate both double negation and negative concord interpretations for sentences with multiple negative expressions (Blanchette 2017 ; Blanchette et al. 2018 ; Blanchette 2019 ). 6 Some researchers have used this evidence to support the idea that Standard English is in fact an inherently negative concord language and that the apparent preference for double negation is due to sociolinguistic factors (Blanchette 2015 ); for others, these facts have been instead taken to suggest that Standard English is a double negation language which shows some concord behavior (Zeijlstra 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here as well, the empirical picture appears more complex than previously described, with some strict NC languages failing to license DN readings entirely, and others allowing them under distinct conditions. Similarly, while NC readings have long been claimed to be unavailable in standard English, recent experimental evidence has shown that they occur quite readily (Déprez 2014;Blanchette & Lukyanenko 2019a;b). These authors argued that NC readings must be part of the grammar of American English, since speakers can assess constraints on their grammaticality independently of whether they acknowledge using them in their own idiolects.…”
Section: Negative Concord and Double Negation Readings Cross-linguist...mentioning
confidence: 99%
“…Or on the contrary, should DN readings be considered as largely irrelevant to the grammar of NC languages, if as Espinal & Prieto (2011) have argued, they are pragmatically-triggered non-compositionally inferable outputs of denial mechanisms akin to metalinguistic negation (Horn 1989)? Related questions also arise about NC readings in DN languages (Zeijlstra 2010;Blanchette & Lukyanenko 2019a). Answers to these questions bear on the validity of syntactic models of negative dependencies that take DN and NC as consequences of syntactic macro-parametric options, or on the contrary, defend that they are both languageinternal options permitted by the grammar (Déprez 2000;de Swart & Sag 2002;de Swart 2009;Iordachioaia 2009;Déprez 2011).…”
Section: Negative Concord and Double Negation Readings Cross-linguist...mentioning
confidence: 99%
“…At its core is the relationship between the subject and the auxiliary, which occur in an order that is non-canonical in both standardized and vernacular Englishes. Two further descriptive characteristics of NAI are that the auxiliary must be negated (e.g., Parrott, 2000;White-Sustaíta, 2010), and the negation appears as the clitic n't as opposed to the marker not (Blanchette, 2015;Matyiku, 2017;Parrott, 2000;Salmon, 2018). Labov et al (1968) and Labov (1972) observed NAI use by vernacular African American and Latinx speakers in New York, and it has also been observed in White Alabama English (Feagin, 1979), West Texas English (Foreman, 1999(Foreman, , 2001Matyiku, 2017), Vernacular Texas English (Salmon, 2018), African American English (Green, 2002(Green, , 2014Parrott, 2000;Sells et al, 1996;Weldon, 1994), and Appalachian English (Montgomery, 2004;Montgomery & Hall, 2004;Tortora & den Dikken, 2010;Wolfram & Christian, 1976).…”
Section: General Usage and Interpretationmentioning
confidence: 99%